Policy recommendations for current relationship between electronic commerce and Mexican SMEs: Theoretical analysis under the vision based on the industry - José G. Vargas-Hernández; David Iván Pérez Rosas (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
The objective of this essay is to present a different approach on the Porter’s five forces model and to make the reader aware of the topic of industrial competence and e-commerce in Mexico. In this essay, the method used is the analytic descriptive. First, the current situation in which SMEs in Mexico are related to e-commerce is exposed, since this last one provides a significant opportunity for the improvement of business results for this class of companies. In addition, a review of the empirical literature is provided in which models that allow measuring the degree of adoption of e-commerce by SMEs are exposed, as well as to understand the behavior of these economic agents with the e-commerce worldwide as in territory Mexican. Finally, as a result, an analysis is carried out under the model of the Porter pyramid in relation to Mexican SMEs and e-commerce.